2020
DOI: 10.31703/gssr.2020(v-i).28
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Relationships of Positive and Negative Organizational Behaviors (OB) with the Productivity of Engineering Students

Abstract: This study explores the relationships between positive and negative Organizational Behaviors and Workaholism; and the relationship of these OBs with productivity and gender of engineering students in Pakistan. Most of the researchers have studied OBs among faculty or administrative staff in universities. The study of these behaviors among students is a new area. An eight-stage innovative qualitative codebook thematic analysis was used to analyze semi-structured interviews from 22 faculty members to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The present research's novel contribution is the explanation of the indirect effects of work ethic (IWE) on productivity through OCB, DDB, CDB, and WA; engineering students exhibit/demonstrate work ethic (IWE in Pakistan having 97% Muslim population) which has a positive effect on their productivity through positive/negative organizational work behaviors/attitudes. This finding is in line with contemporary scholars' findings including Allison et al and Bunce et al [9,14,41,51]. The results also suggested that studying the "independently existing but interrelated distinct work behaviors, attitudes, and ethics" in a wholesome model to understand their combined effects on productivity is a more logical, understandable, and explainable approach.…”
Section: Conclusion and Recommendationssupporting
confidence: 88%
See 3 more Smart Citations
“…The present research's novel contribution is the explanation of the indirect effects of work ethic (IWE) on productivity through OCB, DDB, CDB, and WA; engineering students exhibit/demonstrate work ethic (IWE in Pakistan having 97% Muslim population) which has a positive effect on their productivity through positive/negative organizational work behaviors/attitudes. This finding is in line with contemporary scholars' findings including Allison et al and Bunce et al [9,14,41,51]. The results also suggested that studying the "independently existing but interrelated distinct work behaviors, attitudes, and ethics" in a wholesome model to understand their combined effects on productivity is a more logical, understandable, and explainable approach.…”
Section: Conclusion and Recommendationssupporting
confidence: 88%
“…Ethics are moral judgments of any individual about right and wrong. Many researchers have found that mostly in Muslim countries, people follow Islamic work ethics (IWE) which have effects on their work outcomes, performances, and productivity [41,[50][51][52][53]. We hypothesize in our study that Hypothesis 5 (H5).…”
Section: We and Productivitymentioning
confidence: 88%
See 2 more Smart Citations